Updated taxonomic checklist of Chalcidoidea (Hymenoptera) associated with Bruchinae (Coleoptera: Chrysomelidae) - Pérez-Benavides, A. Lucía; Hernández-Baz, Fernando; González, Jorge M.; Riverón, Alejandro Zaldívar (Zootaxa, 2019)
A taxonomic checklist of Chalcidoidea (Hymenoptera) associated with Bruchinae (Coleoptera: Chrysomelidae) is presented. A total of 139 species of Chalcidoidea or unidentified species to genus are reported as primary parasitoids. The valid name, primary host(s) (animal and plant taxa), distribution and references for each species are listed.